Prevalence of prolonged grief disorder in a sample of female refugees - Regina Steil; Jana Gutermann; Octavia Harrison; Annabelle Starck; Laura Schwartzkopff; Meryam Schouler-Ocak; Ulrich Stangier (BMC Psychiatry, 2019)
Abstract Background Prolonged Grief Disorder (PGD) is a distinct syndrome that follows bereavement. It is different from other mental disorders and is characterized by symptoms such as yearning for the bereaved, or intense emotional pain or distress. Violent loss is one major risk factor for the development of PGD. Objectives PGD has been studied in different populations, mostly in small samples, with only a few of them being representative. Although research highlighted that traumatic experiences paired with challenges related to migration make refugees particularly vulnerable to PGD, PGD has only rarely been studied in refugees. Thus, this article a) examines the prevalence of PGD in female refugees in Germany according to the criteria proposed by Prigerson and colleagues in 2009, and b) associates PGD with other common psychopathology (e.g. anxiety, depression, somatization and trauma). Method A total of 106 female refugees were assessed for bereavement and PGD. Of these 106 individuals, 85 were interviewed using the Prolonged Grief Disorder Scale (PG-13). Symptoms of anxiety and depression were assessed by the Hopkins Symptom Checklist-25 (HSCL-25), somatization was assessed by the Somatization Subscale of the Symptom-Checklist-90 (SCL-90), and the number of witnessed and experienced trauma was assessed by the Posttraumatic Diagnostic Scale (PDS/HTQ). Results Ninety of the 106 participants had experienced bereavement, and among those, 9.41% met criteria for PGD. The most frequent PGD symptoms were bitterness, longing or yearning for the bereaved, and lack of acceptance of the loss. Furthermore, grief symptoms were significantly associated with symptoms of depression, anxiety, somatization, and the number of experienced traumatic events. Conclusion The PGD prevalence rate found corresponds with previous studies, demonstrating that prevalence rates for PGD are especially high in refugees. High prevalence rates of bereavement as well as PGD highlight the need for assessment and specifically tailored treatment of PGD in refugees. PGD goes along with significant psychopathology, which further emphasizes the need for treatment.